Tom and Jerry in US-China Relations - huswatun miswar, syarifah; Miswar, Syarifah Huswatun (Jurnal Multidisiplin West Science, 2024)
In the liberal concept, especially neoliberal, countries that cooperate tend to have less potential for conflict. However, this does not apply to US-China relations which are more often in tension, but until the Biden administration China-America still has a strong dependence in economic relations. The China-US relationship is often referred to as the "Thucydides Trap" but this theory has many shortcomings in explaining reality. After analyzing, it is found that China - America relations are more easily analogized to the relationship between cats and mice in the cartoon series "Tom and Jerry" who are often hostile but occasionally also work together for mutual interests, goals, and security.